2018
DOI: 10.1111/jfpp.13826
|View full text |Cite
|
Sign up to set email alerts
|

Studies regarding the production of a novel yogurt using some local plant raw materials

Abstract: In this study, we evaluated the effect of some Romanian local plant raw materials on the rheological, physicochemical, and sensory properties of natural yogurt. These plants were added as a 2% powder in the set yogurt recipe and the finished products obtained under the same conditions were compared to a control sample. By adding plant powders, the rheological properties of yogurt were improved, the syneresis was reduced, and the water holding capacity of the yogurt samples was increased. The highest values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…According to the results, the control sample was the most unstable and the yogurt with sea buckthorn presented the lowest pH variation (0.03 units) and the sample P3, with blueberry capsules in composition-the lowest variation in water-holding capacity (5.29 units). The same results were observed by Dabija et al, when 2% buckwheat and beetroot powder was added to yogurt, syneresis was lower and water-holding capacity was higher than the control sample [54]. Syneresis is correlated with the acidity of the samples, explaining the increase in syneresis over the shelf life for sample 2.…”
Section: Resultssupporting
confidence: 83%
“…According to the results, the control sample was the most unstable and the yogurt with sea buckthorn presented the lowest pH variation (0.03 units) and the sample P3, with blueberry capsules in composition-the lowest variation in water-holding capacity (5.29 units). The same results were observed by Dabija et al, when 2% buckwheat and beetroot powder was added to yogurt, syneresis was lower and water-holding capacity was higher than the control sample [54]. Syneresis is correlated with the acidity of the samples, explaining the increase in syneresis over the shelf life for sample 2.…”
Section: Resultssupporting
confidence: 83%
“…A sensory study conducted by Dabija et al (2019) also revealed that yogurt with the addition of beetroot powder resulted in a high customer acceptance (19.2). Beetroot powder can also be utilized for bakery applications as a functional ingredient.…”
Section: Applications Of Betalain In the Food Industrymentioning
confidence: 97%
“…Previous studies reported the use of betalains in foods with different formulations, especially as a natural colorant with antioxidant and antimicrobial activities [30]. Regarding the use of betalains in beverages, Dabija et al [31] reported the addition of beet powder in natural yogurt, evaluating its effect on the physicochemical, rheological, and sensory properties of the yogurt. Likewise, Dias et al [32] studied the color stability of fermented soy yogurts with added beet, opuntia, and red radish extracts and evaluated the behavior of the pigments (betalains) during storage.…”
Section: Content Of the Main Individual Betalains And Phenolic Compou...mentioning
confidence: 99%